Feature recess-time sports activities as a school-based intervention to improve fitness in rural Chinese youth - Xiao Hua Huang; Xiao Yu Huang; Fadzilah Abd Rahman (PLoS ONE, 2026)
Background China’s national school health policies face persistent implementation gaps, particularly in rural high schools prioritizing Gaokao. National surveys (2010–2019) documented alarming fitness declines: 50-m sprint speeds decreased (+0.3s boys; + 0.4s girls), pull-ups/sit-ups fell 29%/20%, and standing jumps shortened 6–7 cm. Methods A 16-week cluster quasi-experiment assigned intact rural high school classes (N = 98; age = 16.35 ± 0.48years) to: • Experimental (n = 50): Feature Recess-Time Sports Activities (FRTSA; 5x30-min/week). • Control (n = 48): Standard supervised running. Blinded assessors conducted the National Student Physical Health Standard tests. Results FRTSA elicited significant improvements versus control: • Speed: 50-m sprint ( p < 0.001, η 2 = 0.18, d = 0.75). • Explosive Power: Standing jump ( p = 0.022, η 2 = 0.05, d = 0.41). • Flexibility: Sit-and-reach ( p < 0.001, η 2 = 0.12, d = 0.60). • Strength: Male pull-ups ( p = 0.030, d = 0.41); female sit-ups ( p = 0.029, d = 0.45 ). No endurance benefits emerged (1000m/800m: all p > 0.05, d ≤ 0.18). Conclusion FRTSA is effective in enhancing speed, explosive power, flexibility, and strength, supporting policy integration of structured activity programs in rural schools.